Using Six Sigma Tools to Improve Strategic Cost Management: Management Accounting Perspective - Nanang Shonhadji (Universitas Hayam Wuruk Perbanas, 2016)
The company's commitment to implement Six Sigma has been said to fail, as a quality management strategies, as expected to lead to continuous improvement. This study has its objective to identify the use of Six Sigma as a tool to improve cost management strategies in the production of LED (light emitting diode) on PT TMJ. It uses a case study approach to non-mainstream. The unit of analysis done on the application of six sigma strategies to evaluate quality management performance on the cleaning process of the LED light top-ring used in this study. The result of the evaluation measure phase, generally, informs that the company has increased sigma capability of the base performance so that the company's efforts to reduce the level of disability in circumference above the cleaning process should be defect-free LED light wrinkle, wave and widened in accordance with the target. All these can be said to be successful. The result also informed that at the stage of evaluating the attributes of data processing capability, informed that the company is in the process conditions. The fairly stable production, production process capability are quite capable to meet the specifications of the desired target customers.